Pandemic and new perspectives on living: the role of the smart home - Ciampi, Marina; Sessa, Melissa (Frontiers in Sociology, 2023)
Based on ongoing multidisciplinary research, this essay offers some theoretical and scenario considerations on the transformations of social rituals in housing contexts during the pandemic period. The analysis focuses on living not only understood as a "private" experience, but also as a phenomenon of collective interest, especially in relation to issues concerning health emergencies, risk perception and forms of sociability. In the face of such problems, the sociological perspective has shown its usefulness in providing suitable tools to study the ambivalent and exceptional aspects to which living was exposed during the lockdown period and in the immediate aftermath. Thus, it was chosen to focus attention on the phenomenon of the smart home, an "agent subject", albeit inanimate, of the process of technological transformation of the housing unit, which can be evaluated not only on the level of environmental sustainability, but also on that of social sustainability.